Kesenian Ronggiang Pasaman Group Ranah Saiyo Dari Bentuk Hiburan Ke Bentuk Pertunjukan - Emeilya Batu Bara; Nerosti Nerosti (SENDRATASIK UNP, 2021)
This study aims to reveal the art of Ronggiang Pasaman of Ranah Saiyo group from entertainment to performance form. This is a qualitative research using analytical descriptive method. The main instrument in this study was the researcher it self with primary and secondary data. The data were collected throughliterature study, observation, interview, and documentation. The object of this research was Ronggiang Pasaman Art of Ranah Saiyo group. The results show that Ronggiang is the only entertainment dance which has its own characteristics, uniqueness, and beauty from other entertainment dances in AuaKuniang village. Ronggiang can be seen from the form of presentation. Ronggiang is danced by three or four dancers. There are male dancers and one of which acts as singer. This is due to the fact that in ancient times women were prohibited to dance in crowd by the customs of Aur Kuning community. The place to show Ronggiang performance is not arbitrary because the performanceis arranged as well as possible. Music in Ronggiang is the main support which serves to provide atmosphere and enthusiasm for the dancers and the audiences who watch it. The differences can be seen from the entertainment and performance form Ronggiang. Ronggiang performance usually serves as entertainment for the community. Such entertainment is performed in some events such as Mamasak, maaghak-aghak, youth events, and West Pasaman's Birthday. As for the show, it is usually performed in a special place.